A randomized controlled trial to test efficacy and safety of thrombectomy in stroke with extended lesion and extended time window - Bendszus, Martin; Bonekamp, Susanne; Berge, Eivind; Boutitie, Florent; Brouwer, Patrick; Gizewski, Elke; Krajina, Antonin; Pierot, Laurent; Randall, Gary; Simonsen, Claus Z; Zeleňák, Kamil; Fiehler, Jens; et al. (International journal of stroke, 2019)
RATIONALE: The benefit of thrombectomy in patients with intracranial large vessel occlusion of the anterior circulation has been shown in selected patients in previous randomized controlled trials, but patients with extended ischemic lesions were excluded in the majority of these trials. TENSION aims to demonstrate efficacy and safety of thrombectomy in patients with extended lesions in an extended time window (up to 12 h from onset or from last seen well). DESIGN: TENSION is an investigator-initiated, randomized controlled, open label, blinded endpoint, European, two-arm, postmarket study to compare the safety and effectiveness of thrombectomy as compared to best medical care alone in stroke patients with extended stroke lesions defined by an Alberta Stroke Program Early Computed Tomography Scan score of 3-5 and in an extended time window. In an adaptive design study, up to 665 patients will be randomized. OUTCOMES: Primary efficacy endpoint will be clinical outcome defined by the modified Rankin Scale at 90-day poststroke. The main safety endpoint will be death and dependency (modified Rankin Scale 4-6) at 90 days. Additional effect measures include adverse events, health-related quality of life, poststroke depression, and costs utility assessment. DISCUSSION: TENSION may make effective treatment available for patients with severe stroke in an extended time window, thereby improving functional outcome and quality of life of thousands of stroke patients and reducing the individual, societal, and economic burden of death and disability resulting from severe stroke. TENSION is registered at ClinicalTrials.gov (ClinicalTrials.gov Identifier NCT03094715).
Keywords: senioři; analýza přežití; Thrombectomy; stupeň závažnosti nemoci; Disease Progression; protocols; Stroke; senioři nad 80 let; ischemic stroke; Brain Ischemia; Survival Analysis; Europe; progrese nemoci; Time Factors; Tomography, X-Ray Computed; Acute stroke therapy; výsledek terapie; Evropa; Middle Aged; Fibrinolytic Agents; mužské pohlaví; Adult; mladý dospělý; cévní mozková příhoda; fibrinolytika; trombektomie; Aged, 80 and over; Young Adult; ženské pohlaví; Randomized Controlled Trials as Topic; Humans; therapy; časové faktory; endovaskulární výkony; lidé středního věku; Endovascular Procedures; treatment; dospělí; intervention; randomizované kontrolované studie jako téma; stroke; ischemie mozku; počítačová rentgenová tomografie; Aged; Female; Severity of Illness Index; Treatment Outcome; radiology; lidé; Male